Managing the built heritage of Lima. Notes for the construction of a theoretical framework - Hayakawa Casas, José Carlos (2017)
The urban built heritage is a special and dynamic spectrum of human activity. Proper management of this heritage can become in increasing the quality of life of urban communities that give it meaning. The analysis of representative cases contributes to develop an overview and to systematize their «learned lessons». The integral development of the urban built heritage requires consensus between social partners, optimizing the management of available resources, in a scenario of weak institutions and citizenship, where leadership of manager balances it. This article develops some basic but essential concepts, which allow you to build shared approaches and thoughts about a more holistic and inclusive form of built heritage and facilitates the implementation of a more balanced, sustainable and citizenship management of such cultural property.